Design of Multidimensional Nonlinear Predictive Controller for 3D Crane - Szafrański, Maciej; Piotrowski, Robert (Journal of Automation, Mobile Robotics and Intelligent Systems, 2025)
The paper presents a comprehensive approach to design and implementation of a multidimensional nonlinear control system for a 3D crane. For design purposes, a simulation model of the crane is developed and verified. Proposed are two structures of the control system, which are based on PID controller and predictive control system. The synthesis process is presented. The designed systems are verified in terms of their effectiveness, based on the judgement on the obtained waveforms of controlled variables and integral control indicators. Finally, the two systems are compared with each other, and the conclusions regarding their applicability for this type of system are presented.